Women’s Sexuality and Relationship with Hysterectomy - Herti Marni; Syahredi Syaiful Adnani (Universitas Andalas, 2020)
Sexuality is the most complex component, fundamental and main aspects of human behavior and life. Expressions of sexuality and intimacy are important throughout human life.Sexuality itself includes sex, gender identity and role, sexual orientation, eroticism, satisfaction, intimacy and reproduction. Sexuality is experienced and expressed through thoughts, fantasies, beliefs, attitudes, values, behavior, roles and relationships. Although sexuality includes the above dimensions, not everything can be experienced and expressed by everyone. This is influenced by biological, psychological, social, interactions economic, political, cultural, ethical, legal, religious and spiritual. Hysterectomy is a surgical removal of the uterus, which can be done by vaginal, abdominal, laparoscopic and robotic routes. The definition of